IMPLEMENTASI NILAI-NILAI ISLAM DALAM MEMBENTUK BUDAYA ORGANISASI YANG BERETIKA - Mahdi, Muhammad; Ahmad Farial Wahib H; Khoirul Umam (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study examines the implementation of Islamic values in shaping ethical organizational culture. The research aims to analyze how principles such as honesty, justice, trustworthiness, and accountability influence organizational behavior and decision-making processes. Using a qualitative descriptive method, data were collected through literature review and analysis of relevant studies. Findings show that Islamic values significantly contribute to building an ethical work climate by guiding leaders and employees toward moral conduct, strengthening organizational integrity, and reducing unethical practices. The implications of this study suggest that integrating Islamic ethical principles can enhance performance, support sustainable governance, and foster a culture of responsibility within modern organizations.